Role plays as a teaching-learning strategy to encourage the acquisition of skills. An experience in the Degree in Tourism - ZUMAQUERO GIL, LAURA (Revista Jurídica de Investigación e Innovación Educativa (REJIE Nueva Época), 2018)
This paper exposes the experience carried out through the technique of role play in a subject of introduction to the civil law of the Degree in Tourism. This tool has been used within the teaching modality «practical classes», in order to increase the motivation of students, as well as encourage the acquisition of some of the skills that appear in the guide of the subject and that must be submitted to evaluation. The work also includes the rubric model that has been used to evaluate the acquisition of such skills, as well as the assessment that both the teacher and students make of the activity carried out.